A STUDY ON STUDENTS’ ANXIETY IN SPEAKING OF ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU - Rahma Yulianti; M.Syarfi M.Syarfi; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research is aims to find out the levels of students’ speaking and the dominant type of anxiety that occured in speaking performance of the Third Semester Students of English Study Program FKIP Universitas Riau. The population of this research was 113 students which divided into 6A, 6B and 6C class as total number of the third year English Study Program Students of Universitas Riau. The researcher used cluster random sampling to choose the sample and 6B class had been chosen as the sample of the research which was made up of 30 students. The researcher used a questionnaire to collect the data containing 3 types of anxiety. There were 30 items for questionnaire of speaking anxiety. The questionnaire was adapted from FLCAS (Foreign Language Classroom Anxiety Scale) designed by Horwitz et al (1986). The result of the questionnaire shows that the students’ speaking anxiety is in the anxious level. There were five students (12,82%) in the level of very anxious, twenty-seven students (74,36%) in the level of anxious, five students (12,82%) in the mildly level, zero student (0%) both in relaxed also very relaxed level. It concludes that the highest anxiety scale that occurs in “anxious” caused by test anxiety.Key Words: Speaking, Anxiety, Speaking Anxiety